MEMBANGUN MODEL KEUNGGULAN BERSAING BERKELANJUTAN DENGAN DUKUNGAN MANAJEMEN SUMBER DAYA MANUSIA - Edy Hartono (Riset Manajemen dan Akuntansi, 2019)
The objective is to develop new theoretical models in improving organizational performance through sustainable competitive advantage. Strategy and organization structure and innovation are essential elements for building a differential capability consisting of differential functional, cultural, positional, and regulatory. These differential capabilities will boost the performance of the organization.